Odpowiedź :
Zad. 1
[tex]\dfrac{(1\frac{1}{3}+1\frac{2}{3} \cdot 1,2) :1\frac{2}{3} - (1,75:1\frac{1}{8}-2\frac{1}{3}:5,25) \cdot 0,9}{(5\frac{5}{6} -5,5) \cdot 0,3} = \\\\ = \dfrac{(1\frac{1}{3}+\frac{5}{3} \cdot \frac{12}{10}) :\frac{5}{3} - (\frac{175}{100} :\frac{9}{8}-\frac{7}{3}:\frac{525}{100}) \cdot \frac{9}{10}}{(\frac{35}{6} -\frac{55}{10}) \cdot \frac{3}{10}} =[/tex]
[tex]= \dfrac{(1\frac{1}{3}+\frac{\not{5}^1}{\not{3}_1} \cdot \frac{\not{6}^2}{\not{5}_1}) \cdot \frac{3}{5} - (\frac{7}{\not{4}_1} \cdot \frac{\not{8}^2}{9}-\frac{7}{3}:\frac{21}{4}) \cdot \frac{9}{10}}{(\frac{35}{6} -\frac{11}{2}) \cdot \frac{3}{10}} = \\\\ =\dfrac{(1\frac{1}{3}+2) \cdot \frac{3}{5} - (\frac{14}{9}-\frac{\not{7}^1}{3} \cdot \frac{4}{\not{21}_3}) \cdot \frac{9}{10}}{(\frac{35}{6} -\frac{33}{6}) \cdot \frac{3}{10}} =[/tex]
[tex]=\dfrac{3\frac{1}{3} \cdot \frac{3}{5} - (\frac{14}{9}-\frac{4}{9}) \cdot \frac{9}{10}}{\frac{2}{6} \cdot \frac{3}{10}} =\dfrac{\frac{\not{10}^2}{\not{3}_1} \cdot \frac{\not{3}^1}{\not{5}_1} - \frac{\not{10}^1}{\not{9}_1} \cdot \frac{\not{9}^1}{\not{10}_1}}{\frac{1}{\not{3}_1} \cdot \frac{\not{3}^1}{10}} = \\\\ = \dfrac{2- 1}{\frac{1}{10}} = \dfrac{1}{\frac{1}{10}} = 1 : \frac{1}{10} = 1 \cdot 10 = 10[/tex]
Zad. 2
[tex]\frac{2x-1}{3} -1=\frac{5-2x}{4} +\frac{x-1}{6} +2 \ \ \ |\cdot 12 \\ 4 \cdot (2x-1)-12 = 3 \cdot (5-2x)+2 \cdot (x-1) + 24 \\ 8x-4-12= 15-6x+2x-2+24 \\ 8x - 16= -4x+37 \\ 8x+4x= 37+16 \\ 12x = 53 \ \ \ |:12 \\ x = \frac{53}{12} \\ x = 4\frac{5}{12}[/tex]